Film Moammar Emka’s Jakarta Undercover” Tinjauan Framing Jurnalistik - Adnan, Hafizur Kahfi; Saragih, M. Yoserizal (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This movie presents the dark side of Jakarta from the perspective of a journalist who is the main character in this story. Moammar Emka's Jakarta Undercover is associated with a journalistic review of how the process occurs in the main character investigating the running of crime that is not known by the public in the city of Jakarta. This research uses a qualitative research method with a descriptive approach. The analysis technique used is framing analysis from Zhongdang Pan and Gerald M. Kosicki. The purpose of this research is to find out how the main character framed the events he wanted to write about through articles based on a journalistic point of view. The conclusion in the article obtained that through syntactic, script, thematic and rhetorical structures, researchers analyzed the main character's efforts in making an article, researchers outlined the role of the structures described by Zhongdang Pan and Gerald M. Kosicki in this film. In the movie, the main character conducts research by digging up information through interviews with relevant sources, and seeing firsthand what happened at the scene.